2014
DOI: 10.1108/ijebr-02-2013-0032
|View full text |Cite
|
Sign up to set email alerts
|

What drives learning orientation in fast growth SMEs?

Abstract: Purpose – The purpose of this paper is to investigate drivers of learning orientation (LO) in 253 Australian fast-growth small-to-medium enterprises (SMEs) through an examination of the interrelationships between transformational leadership (TL), human resource (HR) practices, and organizational climate. Design/methodology/approach – CEOs/managers of fast growth SMEs completed either an online or mailout survey. Statistical analyses invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 119 publications
0
10
0
2
Order By: Relevance
“…On the other hand, other scholars on the subject have concluded that when SMEs adopt and develop a learning model based on dynamic capabilities and manage to turn it into a fluid process of knowledge management, the financial performance of the business grows exponentially and is sustained [59,60]. Generally, SMEs can improve their learning systems and financial performance because they are closer to their employees, which makes it easier to capture, transfer and better apply the knowledge learned [50,61]. Therefore, organizational learning is visualized as a capacity that helps to achieve better organizational practices, such as the adoption of social responsibility, and an increase of financial performance in SMEs [62,63].…”
Section: Organizational Learning and Financial Performancementioning
confidence: 99%
“…On the other hand, other scholars on the subject have concluded that when SMEs adopt and develop a learning model based on dynamic capabilities and manage to turn it into a fluid process of knowledge management, the financial performance of the business grows exponentially and is sustained [59,60]. Generally, SMEs can improve their learning systems and financial performance because they are closer to their employees, which makes it easier to capture, transfer and better apply the knowledge learned [50,61]. Therefore, organizational learning is visualized as a capacity that helps to achieve better organizational practices, such as the adoption of social responsibility, and an increase of financial performance in SMEs [62,63].…”
Section: Organizational Learning and Financial Performancementioning
confidence: 99%
“…Two or more MSMEs may have the same set of tangible resources and operate under the same external environment but produce different business performance (Ratnatunga, et al, 2004). The importance of resources varies among MSMEs and depends on the enterprise's goals (Tan, et al, 2014). Researchers should therefore be interested in knowing which resources have the greatest impact on the performance of an enterprise and how they have an influence on the performance.…”
Section: The Enterprise's Pool Of Resourcesmentioning
confidence: 99%
“…A number of research studies highlight the positive effect of a learning culture on enterprise performance (Wang, 2008;Tan, et al, 2014). It can be argued that an enterprise which pays particular attention to knowledge based resources conforms to Kaplan and Norton (1992)'s learning and growth perspective.…”
Section: The Enterprise's Pool Of Resourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…Tan, Smyrnios, and Xiong (2014) claimed that whenever employees 'feel good' about their organization's climate, they perform their tasks better and leaders can anticipate innovative behavior and creativity from them. As a caveat, when the organizational climate emphasizes reliability and efficiency and is not concerned with creativity and innovation, individuals may feel reluctant to take initiative even when they are offered some autonomy (Yukl, 2010).…”
Section: Creating Environments/climates To Promote Innovationmentioning
confidence: 99%